Economic Scenario of Natural Rubber Production and Marketing in Kerala - A.R. Anuja; Amit Kar; V.C. Mathur; G.K. Jha and Pramod Kumar
Kerala is the nearly monopolistic contributor to the natural rubber production of India with 90 % of the total production and 78 % of the area under cultivation in the country. The natural rubber production of the state during 2010-11 was 7.71 lakh tonnes and the coverage under the crop was 5.34 lakh ha. The productivity in Kerala was found to be less compared to the national average i.e., 1419 against 1784 kg/ha, during 2009-10. In Kerala, around 40 per cent of the area as well as 45 per cent of production of rubber comes from three districts; Kottayam, Ernakulam and Pathanamthitta and small holders contributed 92.5 3% to the total production. Trend analysis using index numbers showed that over a period of last 25 years, the area under rubber and its productivity increased to an extent of 46 per cent and 135 per cent respectively and resulted in 244 per cent rise in NR production in Kerala. The instability in area, production and productivity during the period were 2.56, 5.84 and 6.37 per cent respectively. The decomposition analysis showed that the yield effect is contributing nearly two fold to the total production compared to the area effect. Ribbed Smoked Sheet (RSS), Latex Concentrates (LC), Technically Specified Rubber (TSR), Pale Latex Crepe (PLC) and Estate Brown Crepe (EBC) are the important marketing forms of natural rubber. RSS is graded into six grades on the basis of its quality, i.e. RSS 1X, RSS 1, RSS 2, RSS 3, RSS 4 and RSS 5. Rubber marketing structure of the state consists of three separate sectors viz. individual sector, co-operative sector and corporate sector. Rubber mark, RUBCO and RPSs are the three major players in the cooperative sector and their interventions in the market reduce the influence of middlemen ensuring more return to the producers